Antibacterial and Antioxidant Activities of Slender Amaranth Weed - AKBAR,M. (2020)
ABSTRACT: In the present study, antibacterial and antioxidant [1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity] activities of a weed, slender amaranth (Amaranthus viridis L.) were investigated. Extracts of different plant parts were prepared in n-hexane, chloroform and ethyl acetate. Antibacterial activity was measured by using 100 mg mL-1 concentration extracts against 4 deadly phytopathogenic bacterial species viz. Pseudomonas syringae Van Hall, Ralstonia solanacearum Smith, Erwinia carotovora (Jones), Holland and Xanthomonas axonopodis Hasse. In antioxidants assays, 10, 20 and 30 mg mL-1 extracts were used keeping DPPH as control. In these bioassays, ethyl acetate fraction of A. viridis leaf exhibited the best antibacterial and antioxidants activity. Ethyl acetate leaf fraction showed the highest inhibition zone diameter (IZD) where it caused 21 mm IZD against P. syringae and 19 mm IZD against E. carotovora. This extract also showed 22, 52 and 84% antioxidant activity at 10, 20 and 30 mg mL-1 concentrations, respectively. Previously there is no report available that describes antibacterial activity of root extract of A. viridis against P. syringae. Moreover, antioxidant activity of stem and root extracts in n-hexane, chloroform and ethyl acetate was investigated first time in the world. It was concluded that the biological activities observed during the present investigation may be due to the presence of bioactive constituents that can be harnessed as natural antibacterials and antioxidants.